Application of Big Data Technology in Water Conservancy Project Informatization Construction. Issue 1 (May 2021) - Ni, Xudong; Hou, Xiaoyue
Abstract: In order to better develop the cause of water conservancy project, improve the quality of water conservancy project construction, and bring more benefits to the public, this paper expounds the current situation of water conservancy project informatization construction in China through theoretical analysis, discusses the feasibility of big data in water conservancy project informatization construction, and points out the specific application of big data technology, so as to achieve the purpose of water conservancy project informatization construction.